Biomedical Applications of Nanoparticles - Millot, Nadine (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book provides an overview of the design and physico-chemical properties of nanoparticles developed for biomedical applications such as targeting and detection of pathologies, nanovectorization of drugs, radiosensitization, metal detection, and nanocomposite implants. The considerations necessary when developing a new nanomedicine are also developed, including toxicological investigation, biodistribution, and efficacy. This book provides an accurate and current representation of the field by addressing the promises and hurdles of nanomedicine via 20 different pertinent studies. Covering a wide range of areas, this book is an excellent partner for physico-chemists, doctors, pharmacologists, and biochemists working on nanosciences dedicated to medicine, both in industry and in academia.